The diversity of mammals and their distribution in some mountains of Kazakh Upland (Eurasian Journal of Ecology, 2018)
In this article the results of investigations concerning the diversity ofmammals in some mountains (Arganaty, Ulytau, Ortau, Aktau and Kyzylaray) of Kazakh Upland and peculiarities of their distribution in these areasare represented.Based on study results it was shown, that there is different theriofauna composition in different mountains. There were identified41 species of mammals. This represents approximately 46% of animals inCentral Kazakhstan (n=89). Among them in Arganaty in summer season14 species dwell, in Ulytau – 12, Ortau – 16, Aktau – 17 and Kyzylaray – 27 species of theriofauna dwell. The proportion of species is alsovariable. For example, in Arganaty – 16,3% of species, Ulytau – 13,9%,Ortau – 18,6%, Aktau – 19,8%, Kyzylaray – 31,4% of all mammals species were identified. There is also the similarity in species composition.The similarity in fauna composition decrease from west to east. Indicies ofsimilarity rate of mammal’s fauna are higher in Aktau and Ortau, as well asin UlytauamdArganaty Mountains. There was recorded the highest rangein fauna similarity of mammals dwell in Kyzylarai mountain and in the areas to the west of it. In mountains, where investigations were preformed,there were recorded 13 rare species of mammals. They do constitute about31,7% (n=41) of theriofauna.Key words: Kazakh Uplands, Central Kazakhstan, mammals, diversity,similarity coefficient, rare species.